Co‐design of a filtering antenna based on multilayer structure. Issue 2 (16th December 2019) - Cui, Jingyu; Zhang, Anxue; Yan, Sen
Abstract: In this paper, a co‐design of filtering antenna based on multilayer structure is proposed for modern wireless communication systems. The filtering antenna system consists of a filtering network partly designed on two dielectric substrates and a Г‐shaped antenna, which performs as both a radiator and the last order of the filter. An effective co‐design method based on parameter extraction for impedance matching can significantly reduce the optimization time. Furthermore, a slot is grooved on the common ground, which is shared by the antenna and the filter to realize the feeding of the resonator. A prototype of the filtering antenna was fabricated and measured, and a good agreement is achieved. The tested results show that the filtering antenna features a 2.7% bandwidth, 2.2 dBi gain at 2.6 GHz and −20 dB out of band rejection at 5 × f 0 . The size of the design is 0.29λ g × 0.23λ g .